Music Upper Limb Therapy—Integrated: An Enriched Collaborative Approach for Stroke Rehabilitation - Raghavan, Preeti; Geller, Daniel; Guerrero, Nina; Aluru, Viswanath; Eimicke, Joseph P.; Teresi, Jeanne A.; Ogedegbe, Gbenga; Palumbo, Anna; Turry, Alan (Frontiers in Human Neuroscience, 2016)
Stroke is a leading cause of disability worldwide. It leads to a sudden and overwhelming disruption in one’s physical body, and alters the stroke survivors’ sense of self. Long-term recovery requires that bodily perception, social participation and sense of self are restored; this is challenging to achieve, particularly with a single intervention. However, rhythmic synchronization of movement to external stimuli facilitates sensorimotor coupling for movement recovery, enhances emotional engagement, and has positive effects on interpersonal relationships. In this proof-of-concept study, we designed a group music-making intervention, Music Upper Limb Therapy-Integrated (MULT-I), to address the physical, psychological and social domains of rehabilitation simultaneously, and investigated its effects on long-term post-stroke upper limb recovery. The study used a mixed-method pre-post design with one-year follow up. Thirteen subjects completed the 45-minute intervention twice a week for six weeks. The primary outcome was reduced upper limb motor impairment on the Fugl-Meyer Scale. Secondary outcomes included sensory impairment (two-point discrimination test), activity limitation (Modified Rankin scale), well-being (WHO well-being index), and participation (Stroke Impact Scale). Repeated measures ANOVA was used to test for differences between pre- and post-intervention, and one-year follow up scores. Significant improvement was found in upper limb motor impairment, sensory impairment, activity limitation, and well-being immediately post-intervention that persisted at 1 year. Activities of daily living and social participation improved only from post-intervention to one-year follow up. The improvement in upper limb motor impairment was more pronounced in a subset of lower functioning individuals as determined by their pre-intervention wrist range of motion. Qualitatively, subjects reported new feelings of ownership of their impaired limb, more spontaneous movement, and enhanced emotional engagement. The results suggest that the MULT-I intervention may help stroke survivors re-create their sense of self by integrating sensorimotor, emotional and interoceptive information, and facilitate long-term recovery across multiple domains of disability, even in the chronic stage post-stroke. Randomized controlled trials are warranted to confirm the efficacy of this approach. Clinical Trial Registration: National Institutes of Health, clinicaltrials.gov, NCT01586221.